Incentive Methods of Traditional and Lean Production - Nagy, Erzsébet Zsuzsanna (International Journal of Engineering and Management Sciences, 2016)
Many research deals with the lean management, but mainly related to the topic of operational management. The target of the author to investigate the lean production can be found there any incentives that could be support of the changed labour market. After the labor market outlook, which may help us to understand the actualities of the topic, grouping the incentive methods based on the model of Hay Group's happening, which is collected on the basis of literature lean processing methods. An identifiable differences in the grouping of lean and related traditional production incentives, which are sometimes more supportive of employees' commitment to the company.